Unveiling the Importance of Precursor Preparation for Highly Efficient and Stable Phenethylammonium‐Based Perovskite Solar Cells. Issue 4 (5th February 2020) - Lee, Da Seul; Kim, Jincheol; Bing, Jueming; Zheng, Jianghui; Yun, Jae Sung; Seidel, Jan; Lim, Sean; Green, Martin A.; Huang, Shujuan; Ho-Baillie, Anita W. Y.
Abstract : For the fabrication of low‐dimensional perovskite solar cells, understanding the effect of precursor preparation on film formation is critical to achieve high‐quality perovskite film and, therefore, high efficiency in related solar devices. Herein, the two methods to prepare phenethylammonium‐based mixed perovskite precursors with the same chemical composition are reported. These methods are called 1) different phase (DP) and 2) same phase (SP) methods as the former involves the mixing of a 3D perovskite precursor with a 2D perovskite precursor, whereas the latter involves the mixing of quasi‐2D perovskite precursors. The films prepared by these methods are characterized by X‐ray diffraction, Kelvin probe force microscopy, and scanning electron microscopy, revealing different perovskite structures. The power conversion efficiency (PCE) of the champion cells by DP and SP methods reaches 19.1% and 18.9%, respectively. Results of the aging test show a dramatic improvement in the stability of SP perovskite devices maintaining 86% of its initial performance after exposure to a relative humidity (RH) 8 ± 5% for 1000 hr and over 80% of its initial PCE after continuous 1 sun illumination (including UV) at RH 70%. The new insights provided by this work are important to design perovskite precursor preparation methods for the best device performance and stability. Abstract : The use of two precursor preparation methods for the deposition of phenethylammonium‐containing organic‐inorganic hybrid perovskite films for photovoltaic applications is reported. It is found that film properties, photovoltaic device performance, and stability differ depending on the precursor preparation methods. These new insights are important for optimizing precursor preparations for lower dimensional perovskite films to achieve the best device performance and stability.